Nature of inheritance of productivity factors by tomato F1 hybrids in greenhouse - В. А. Кравченко; О. М. Крижанівська (Plant Varieties Studying and Protection)
The article features results of studying F1 hybrids of tomato inheriting productivity factors. 21 original hybrid forms and 57 F1 tomato hybrids in green-house have been studied. The efficiency of selecting genotype of valuable plants by genotype is substantiated.